Manfaat Mengonsumsi Air Zam-Zam dalam Persfektif Islam dan Sains - Dwi Putri Oktaviani; Agus Fakhruddin (Transformatif, 2021)
Zam-zam water is water that appeared in the period of Prophet Ismail as., Long before the birth of Prophet Muhammad SAW. Zam-zam water has received testimony and direct justification from the Prophet Muhammad as the best water on earth which contains many benefits. Explicitly, the properties of zam-zam water are listed in the hadith, which is considered authentic quality according to scholars. The article examines the existence of zam-zam water from a hadith perspective and a scientific perspective. In the hadith perspective. This article also examines the benefits of Zamzam water, through a scientific approach, zam-zam water will be more deeply researched so that a scientific fact can be found that the substances contained and molecules arranged in zam-zam water is better than other substances or water molecules. . So, the Prophet Muhammad's justification for zam-zam water is proven by the truth of the facts of modern scientific research.